Age differences in immunity to human seasonal coronaviruses and the immunogenicity of ChAdOx1 nCoV-19 (AZD1222)Research in context - Sandra Belij-Rammerstorfer; Emma Sheehan; Grace Li; Sagida Bibi; Daniel Wright; Merryn Voysey; Cameron Bissett; Ninisha Barman; Susana Camara; Audrey Au Yong; Sue Ann Costa Clemens; Mae Harris; et al. (EBioMedicine)
Summary: Background: ChAdOx1 nCoV-19 (AZD1222) vaccine was widely deployed to protect against severe COVID-19 in adults, but the relationship between pre-existing immunity to human seasonal coronaviruses (HCoVs) and vaccine-induced SARS-CoV-2 (SCoV2) response across age groups remains unclear. Methods: We analysed SCoV2 and HCoVs antibody profiles in UK volunteers (aged 6–≥70), assessing antibody levels, avidity, and FcγR binding after receiving one or two doses of ChAdOx1 nCoV-19. Adult cohorts from trials in Brazil and Kenya were also included to evaluate geographical impacts on baseline HCoVs and SCoV2 induced response. Findings: In the UK cohort, younger individuals had higher SCoV2 IgG, avidity, FcγR binding and cross-reactivity, particularly towards OC43 and HKU1. The greatest differences were seen after the first dose of ChAdOx1 nCoV-19, but these effects diminished after the second dose. Although baseline HCoVs IgG varied geographically, similar trends were observed across adult cohorts with younger adults showing higher SCoV2 IgG compared to older adults (UK and Brazil). Interpretation: These findings contribute to a better understanding of the immunogenicity of ChAdOx1-based vaccines in various age groups. Determining whether this applies across other vaccines using same platform is essential for evaluating the viability of one-dose regimens in outbreak responses. Funding: The clinical trials COV002, COV003, COV004, and COV006 were made possible by funding from Astra Zeneca, the NIHR and the University of Oxford, UK Department of Health and Social Care, through the UK National Institute for Health and Care Research, the Wellcome Trust (220991), and Innovate UK (project 971614).